Case report: An unusual case of desmin myopathy associated with heart failure and arrhythmia - Liu, Xuhan; Liu, Yuan; Li, Bo; Wang, Lin; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Desmin myopathy is a novel desmin (DES) indel mutation causes severe atypical cardiomyopathy as well as atrioventricular block and skeletal myopathy. The mutation of the gene of nodal tail causes myocardial injury. Rarely, desmin myopathy causes bilateral ventricular changes. Case presentation: We present a case of 48-year-old man admitted with dyspnea and edema of both lower extremities. Due to bilateral lower limb weakness and calf muscle atrophy, gene sequencing was performed. The results showed that there was a pure missense mutation in the 8th exon region of DES gene (c.1366G>A), encoding amino acid p.G456R (glycine>arginine). Supplementary examination suggests a high possibility of heart failure, atrial flutter and desmin myopathy. Atrial flutter was treated by radiofrequency ablation. The clinical symptoms were stable after oral administration of rivaroxaban, coenzyme Q10 and sakobactrum valsartan sodium. Conclusion: In our case, mutation results are the gold standard for diagnosis of nodular myopathy. Cardiac magnetic resonance can define the extent and degree of cardiomyopathy and quantitatively evaluate cardiac function. At present, there is a lack of specific treatment for proteolytic myopathy. Therefore the treatment for heart failure proves effective. Due to multiple systems are involved, early diagnosis and multidisciplinary management are critical to improving patient outcomes.